Long‐term survival after low‐dose‐rate brachytherapy for prostate cancer: the Royal Surrey experience. (22nd September 2021) - Uribe‐Lewis, Santiago; Uribe, Jennifer; Bourke, Vincent; Deering, Claire; Higgins, Donna; Mehta, Sheel; Mikropoulos, Christos; Otter, Sophie; Perna, Carla; Khaksar, Sara; Laing, Robert; Langley, Stephen
Abstract : Objectives: To assess the long‐term treatment efficacy of low‐dose‐rate (LDR) brachytherapy for the treatment of localized prostate cancer. Patients and Methods: Cause‐of‐death annotation in our prospective database was supplemented with death certificate information obtained via an internal audit of patients treated from 1999 to 2017 with LDR prostate brachytherapy as monotherapy or as combination with androgen deprivation therapy and/or external beam radiotherapy. Overall and disease‐specific survival were the primary outcomes, estimated with Kaplan–Meier and competing risks multi‐state models. Clinical variables influencing mortality were assessed with Cox proportional hazards regression in a sub‐analysis of men to assess the predictive value of prostate‐specific antigen (PSA) level at 48 months post implant. Results: The audit process began in October 2017 and culminated in June 2020 with a curated series of 2936 patients. All‐cause and prostate cancer‐specific death prevalence were 11% and 2.9%, respectively. The median (range) follow‐up time was 10 (3–21) years and the median (range) time to death from any cause was 9 (3–21) years. At 15 years post implant the overall and prostate cancer‐specific survival probability were 81% and 95%, respectively. The 15‐year cumulative incidence rates of death not due and due to prostate cancer were 14% and 5%, respectively. A greater risk of death due to prostate cancer was conferred by increasing age at therapy (hazard ratio [HR] 1.1, P < 0.001), advanced clinical stages relative to T1a‐T2a (HR 1.9, P = 0.048 for T2b; HR 2.7, P = 0.023 for T2c‐T3b) and a 48‐month PSA level >1.0 ng/mL (HR 6.8, P < 0.001). Conclusion: This study constitutes the largest retrospective analyses of long‐term mortality outcomes from prospectively collected prostate brachytherapy data and confirms the excellent treatment efficacy of LDR prostate brachytherapy for localized prostate cancer. T2 clinical stage subdivisions and 48‐month PSA level >1.0 ng/mL appear to be strong indicators of prostate cancer‐related survival.